2004
DOI: 10.1002/jmri.20213
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral neoplastic compression fractures: Assessment by dual‐phase chemical shift imaging

Abstract: Purpose:To compare normal vertebrae with vertebrae with neoplastic compression fractures by means of opposedphase (OP) and in-phase (IP) gradient-echo (GRE) imaging. Materials and Methods:On OP and IP T1-W GRE images (obtained at 1.5 T with the fast low-angle shot (FLASH) technique) of dual-phase chemical shift sequences, we compared the signal intensity ratios (SIRs) of normal and compression-fractured vertebrae in 108 patients. Dualphase chemical shift sequences were measured in three groups of vertebral bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 15 publications
6
37
0
1
Order By: Relevance
“…Proton chemical shift MR imaging has been suggested as a valuable addition to a standard MR imaging protocol for the study of the bone marrow in vivo (4,(13)(14)(15)(16). In the present article, chemical shift imaging refers to in-phase and opposedphased imaging (acquired with single or separate sequences) (17), although it 2) 20 seconds after contrast agent administration shows avid early arterial enhancement in the lesion, in keeping with its malignant nature.…”
Section: Chemical Shift Imaging (Anatomic Technique)mentioning
confidence: 99%
“…Proton chemical shift MR imaging has been suggested as a valuable addition to a standard MR imaging protocol for the study of the bone marrow in vivo (4,(13)(14)(15)(16). In the present article, chemical shift imaging refers to in-phase and opposedphased imaging (acquired with single or separate sequences) (17), although it 2) 20 seconds after contrast agent administration shows avid early arterial enhancement in the lesion, in keeping with its malignant nature.…”
Section: Chemical Shift Imaging (Anatomic Technique)mentioning
confidence: 99%
“…Eito K et al (2004) [18] also found similar findings, he stated significant difference in SIR between benign and malignant fractures, but noted that some of the benign VCs did not suppress on the opposed-phase images. In the present study, we observed that post contrast enhancement were seen on both malignant and benign VCs; however, posterior element involvement enhancing epidural, pre-and para-vertebral masses were noted in higher percentage in malignant VCs.…”
Section: Quantitative Studymentioning
confidence: 58%
“…Erly, Oh E.S. et al (2006), [16] David Disler et al (1997), [17] and Eito K et al (2004) [18] used similar cut-off value in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In chemical shift MRI, the presence of microscopic fat will result in signal loss on the opposedphase images when compared to the in-phase images within a voxel [8,9]. Hence, CSI has been utilized to identify microscopic fat within skeletal lesions with the aim to distinguish benign from malignant marrow replacement processes [10][11][12][13][14][15][16]. Most recently, Kohl and co-workers evaluated the accuracy of CSI in the diagnosis of indeterminate skeletal lesions of the pelvis.…”
Section: Introductionmentioning
confidence: 99%